2006
DOI: 10.1038/nn1630
|View full text |Cite
|
Sign up to set email alerts
|

Role of p21-activated kinase pathway defects in the cognitive deficits of Alzheimer disease

Abstract: Defects in dendritic spines are common to several forms of cognitive deficits, including mental retardation and Alzheimer disease. Because mutation of p21-activated kinase (PAK) can lead to mental retardation and because PAK-cofilin signaling is critical in dendritic spine morphogenesis and actin dynamics, we hypothesized that the PAK pathway is involved in synaptic and cognitive deficits in Alzheimer disease. Here, we show that PAK and its activity are markedly reduced in Alzheimer disease and that this is ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
303
4
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(331 citation statements)
references
References 47 publications
19
303
4
1
Order By: Relevance
“…These findings suggest that alterations in the mechanisms controlling the actin cytoskeleton are associated with the remarkable synaptic changes observed in these mice. Our findings are in line with previous studies indicating that drebrin, cortactin, and other actin regulators are affected in AD (Arsenault et al., 2013; Mota et al., 2014; Zhao et al., 2006). Drebrin is abundant within dendritic spines because it is required for actin clustering and the synaptic targeting of PSD95, and the suppression of drebrin expression results in a decrease in spine density (Takahashi, Mizui & Shirao, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that alterations in the mechanisms controlling the actin cytoskeleton are associated with the remarkable synaptic changes observed in these mice. Our findings are in line with previous studies indicating that drebrin, cortactin, and other actin regulators are affected in AD (Arsenault et al., 2013; Mota et al., 2014; Zhao et al., 2006). Drebrin is abundant within dendritic spines because it is required for actin clustering and the synaptic targeting of PSD95, and the suppression of drebrin expression results in a decrease in spine density (Takahashi, Mizui & Shirao, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the reduced AMPAR activity observed in 3xTg‐AD mice could lead to drebrin loss in the postsynaptic sites in this animal model, thereby contributing to the observed dendritic spine changes. Drebrin is also regulated by p21‐activated kinase (PAK), and several studies have shown that PAK is also reduced in AD animal models, as well as in human AD brains (Arsenault et al., 2013; Kojima & Shirao, 2007; Zhao et al., 2006). In addition, overexpression of active PAK prevents the drebrin loss induced by soluble Aβ 1‐42 oligomers, whereas pharmacological PAK inhibition in 3xTg‐AD mice leads to drebrin loss as well as memory impairments in adult mice (Arsenault et al., 2013; Zhao et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of active PAK reverses these effects of Ab oligomers. 22,23 Cofilin also has a key role in the loss of dendritic spines induced by Ab. 24 These observations all indicate that activation/dephosphorylation of cofilin is a key component of Ab-induced neurotoxicity at multiple levels.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, defects in PAK signaling have also been associated with cognitive deficits in Alzheimer disease (AD) [92]. AD is characterized by progressive loss of neurons in selected brain regions, extracellular accumulations of amyloid beta (Aß), and intracellular fibrils containing hyperphosphorylated tau [51].…”
Section: Pak3mentioning
confidence: 99%